DESIGN AND DEVELOPMENT OF TEMPERATURE CONTROL SYSTEM USING HYBRID STEPS PHASE CONTROL WITH ON-OFF CONTROL IN HIGH TEMPERATURE FURNACE BASED ATMEGA16A MICROCONTROLLER - Firdiansyah, Hermawan; Darmawan, Hari Arief; Masruroh, Masruroh (Physics Student Journal, 2014)
Design and development of temperature control system using hybrid steps phase control with on-off control in high temperature furnace based ATmega16A microcontroller has been done. The product of this design is a temperature control device in high temperature furnace wich consists of type-k thermocouple as temperature sensor, ATmega16A microcontroller as processor, keypad 4x4 and lcd 16x2 as interface between device and user, and solid state relay as swicthing element. The device works at range of 24 ÂºC to 1212 ÂºC. For the same set-points, the experiment results show that hybrid steps phase control with on-off control is effective to reduce maximum overshoot than just only using on-off control. If set-point used is higher, then it will reduce maximum overshoot and steady state error.